Weighted Central BMO Spaces and Their Applications. (4th August 2021) - Zhao, Huan; Liu, Zongguang
Abstract : In this paper, the central BMO spaces with Muckenhoupt A p weight is introduced. As an application, we characterize these spaces by the boundedness of commutators of Hardy operator and its dual operator on weighted Lebesgue spaces. The boundedness of vector-valued commutators on weighted Herz spaces is also considered.